The Effect of Clinical and Leadership Employee Engagement on Nurse Retention with Resilience as An Intervening Variable at Siloam Kebon Jeruk Hospital - Melissa, Melissa; Kusumapradja, Rokiah; Jusad, Idrus (Alta Dharma Publisher, 2025)
Nursing shortages and high rates of staff turnover are pressing issues that can disrupt health service delivery and increase the costs of recruiting new staff. A similar situation also occurred at Siloam Kebon Jeruk Hospital, which underlines the need to conduct this research. This study aims to examine the influence of clinical leadership and employee involvement on nurse retention at Siloam Kebon Jeruk Hospital, with resilience as a mediating factor. This research is a quantitative study with a cross sectional approach involving 262 respondents. The research sample was taken using the Simple Random Sampling technique. Nurses were surveyed using quantitative techniques to collect data. These findings suggest that clinical leadership and employee engagement have a significant impact on nurse retention, both directly and indirectly, through resilience. Effective clinical leadership fosters a pleasant work environment, enhancing nurses' professional growth and job satisfaction. This study shows that employee engagement can build commitment and reduce turnover rates. The findings of this study suggest that supporting solid clinical leadership and active nurse engagement can significantly increase nurse retention, thereby ensuring consistent, high-quality healthcare services.